Functional features of natural killer cells in acute myeloid leukemia - K. A. Nikiforova; I. V. Galtseva; E. N. Parovichnikova (Онкогематология)
Natural killer cells are a key component of the innate immune system in the fight against tumors. However, in acute myeloid leukemia there is a decrease in the functional activity of these cells. Their activity is under constant control of one or more inhibitory receptors and depends on the balance of inhibitory receptors activation and activating receptors stimulation. This review examines the key inhibitory and activating receptors of natural killer cells and summarizes literature data describing changes in their expression in patients with acute myeloid leukemia.